Conjunctive markers of contrast in English and French from syntax to lexis and discourse - Dupont, Maïté (Studies in corpus linguistics, 2021)
"Situated at the interface between corpus linguistics and Systemic Functional Linguistics, this volume focuses on conjunctive markers expressing contrast in English and French. The frequency and placement patterns of the markers are analysed using large corpora of texts from two written registers: newspaper editorials and research articles. The corpus study revisits the long-standing but largely unsubstantiated claim that French requires more explicit markers of cohesive conjunction than English and shows that the opposite is in fact the case. Novel insights into the placement preferences of English and French conjunctive markers are provided by a new approach to theme and rheme that attaches more importance to the rheme than previous studies. The study demonstrates the significant benefits of a combined corpus and Systemic Functional Linguistics approach to the cross-linguistic analysis of cohesion"--